History of a Sicilian antifascist, professor of classics: Carmelo Salanitro (Adrano, 1894 – Mauthausen, 1945) - Gianotti, Gian Franco (ΠΗΓΗ/FONS, 2019)
Based on a recent book (Pietro Scalisi, L’onore e la viltà. In Memoria di Carmelo Salanitro Martire del Libero Pensiero, 2016), the article traces the life and the witness of freedom of Carmelo Salanitro, a Sicilian anti-fascist condemned by the Italian dictatorship and died in a German extermination camp. In the biography of Salanitro stands out the close link between classical studies, teaching of Latin and Greek and the pursuit of freedom: an exemplary relationship in the European history of the first half of the 20th century.